2005
DOI: 10.1111/j.1467-9353.2005.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Food Assistance in Helping Food Insecure Households Escape Hunger*

Abstract: E very year, the federal government spends a substantial sum on food assistance-totaling $41.8 billion in 2003 (Oliveira). As a result, there is a great deal of interest in assessing the role that food assistance programs play in helping low-income families maintain nutritional adequacy. One outcome of interest is household food security, a measure developed by the U.S. Department of Agriculture (USDA) in the 1990s which indicates whether all members of a household have access, at all times, to enough food for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…For instance, food stamp recipients are consistently found to have higher levels of food insecurity than low income non-recipients, a result generally attributed to self-selection among eligible persons with the greatest need. Researchers have used a variety of strategies to control for selection, includ-ing household fixed-effect models (Wilde & Nord, 2005), two-stage approaches (Gundersen & Oliveira, 2001), and limiting the sample to households that have experienced hunger in the past (Kabbani & Kmeid, 2005). While such approaches are able to reduce and sometimes eliminate the positive association between food stamp receipt and food insecurity, most research has not documented positive benefits of food stamp participation on food security outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, food stamp recipients are consistently found to have higher levels of food insecurity than low income non-recipients, a result generally attributed to self-selection among eligible persons with the greatest need. Researchers have used a variety of strategies to control for selection, includ-ing household fixed-effect models (Wilde & Nord, 2005), two-stage approaches (Gundersen & Oliveira, 2001), and limiting the sample to households that have experienced hunger in the past (Kabbani & Kmeid, 2005). While such approaches are able to reduce and sometimes eliminate the positive association between food stamp receipt and food insecurity, most research has not documented positive benefits of food stamp participation on food security outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Studies have also found that SNAP benefit amounts are associated with lower food insecurity among select populations, including SNAP participants (Rose, Gundersen, and Oliveira 1998) and households that experienced hunger in the past year (Kabbani and Kmeid 2005). …”
mentioning
confidence: 99%
“…Dunifon and Kowaleski-Jones (2003) found that food insecurity rates are higher among children receiving NSLP (24% vs. 5%), reflecting higher use of the program by those most in need. In contrast, Kabbani and Kmeid (2005) found that participants in the NSLP were less likely to be food insecure in comparison to eligible non-participants. The most recent work on this topic is by Gundersen, Kreider, and Pepper (in press) who addressed the dual issues of selection into NSLP (as with SNAP, children are generally thought to be negatively selected into NSLP) and misreporting of NSLP status (as with SNAP, misreporting is endemic on surveys).…”
Section: Public Food Assistance Programsmentioning
confidence: 76%